Influence of basic and specific motor abilities on swimming results - Jorgic, B.; Okicic, T.; Aleksandrovic, M.; Madic, D. (Acta Kinesiologica, 2010)
Sports or competitive swimming is one of cyclic sports in which the form and manner of performance are dominated by relatively simple movements, which are always the same and which are alternately repeated during swimming a certain technique. Since swimming is the movement or motor activity of man, it is necessary to study the influence of certain motor skills on the results in swimming. The aim of this study was to determine the influence of certain basic and specific motor abilities on the results in swimming the 100-meter crawl technique for swimmers aged from 9 to 12 years. The sample consisted of 30 swimmers who are members of the swimming club "Niš 2005" from Niš, with swim experience of at least two years. Thirteen tests were used for the assessment of motor skills (predictor`s variables), 8 for evaluation of basic and 5 to assess specific motor abilities. The result of swimming in the 100 meter crawl was criterion variable. Regression analysis was used to determine the influence. Based on the results of basic motor skills it can be concluded that the whole system of applied variables have statistically significant effect on the result of the crawl, and variables: throw medicine ball in the prone position-MBAC, long jump from a standing-MSKD and deep bend-MDPR have a single statistically significant influence. When it comes to specific motor abilities, a whole system of applied variables also has statistically significant influence on the result in crawl, while individually statistically significant influence have variables: the absolute speed of swimming- SABR and swimming rate-STP. It can be concluded, based on these results that working with young swimmers require planning of trainings for the development of motor abilities of which the result depends on.